THE POLITICS OF ZAKAT MANAGEMENT IN INDONESIA: The Tension Between BAZ and LAZ (JOURNAL OF INDONESIAN ISLAM, 2013)
The new Act of zakat management No. 23 Year 2011 has changed the position of private zakat management (LAZ; Lembaga Amil Zakat) which has no clear relationship with semi-governmental zakat management in the Act of Zakat Management No. 38 year 1999. This paper found that many debates arise especially on the position of private zakat management that has to work under the coordination of semi-governmental zakat management. Many data has shown that private zakat management has reached tremendous achievement compared to the semi-governmental zakat management. Based on this fact, this paper argues that zakat institutions in Indonesia needs to be managed properly without sacrificing the social capital i.e. the participation of private zakat management. This paper proposes that private zakat management needs to be given more spaces in optimizing the collecting and distributing zakat funds in Indonesia. The answer for this problem is building the regulator body for zakat management in Indonesia.